Nutritional status of hemodialysis patients - Panjkota Krbavčić, Ines (Array, 2019)
Hemodialysis patients are vulnerable population group and they, among other, should take special care on food and fluid intake with emphasis on energy, potassium, phosphorus, sodium and protein intake. The nutritional status of patients (n=14) was assessed through measurement of body weight, body height, upper arm circumference, lower leg circumference and handgrip dynamometry; as well as selected biochemical parameters: urate concentration, calcium and phosphate levels, total protein, creatinine, albumin and globulin ratio and C-reactive protein; and dietary assessment method: 3-day food record (3DD). Using range between 18.5 and 24.9 kg/m2 as cut-off, 35.7 and 57% of patients were classified as adequately nourished and overweight, respectively. According to results of 3DD, most of the subjects are supposed to align their micro- and macro- nutrients intake with the recommendations, with emphasis on the increasing intake of protein and energy as well as on decreasing intake of potassium, phosphorus, sodium and energy.